Using human-centered design to develop and implement a pediatric mental health care access program - Lee, Chuan Mei; Jeung, Joan; Yonek, Juliet C.; Farghal, Mahmoud; Steinbuchel, Petra (Frontiers in Psychiatry, 2024)
In 2019, the University of California at San Francisco (UCSF) launched the Child and Adolescent Psychiatry Portal (CAPP), a pediatric mental health care access (PMHCA) program providing remote mental health consultation services to pediatric primary care providers (PCPs) throughout Northern and Central California. The development and implementation of CAPP was guided by Human-Centered Design (HCD), an iterative, rapid-paced innovation process focusing on stakeholders’ needs and experiences, which shaped the development of CAPP’s programs. The resulting key programmatic elements are designed for pediatric workforce development: 1) PCP consultation with a child and adolescent psychiatrist via a telephone warmline; and 2) training and education for providers. CAPP has grown rapidly since its launch, having enrolled 1,714 providers from 257 practices spread across 36 counties and provided 3,288 consults on 2,703 unique lives as of August 2023. Preliminary evaluation findings indicate high PCP satisfaction with CAPP’s services, despite continued challenges of integrating behavioral health into primary care. Throughout the HCD and implementation process, multidisciplinary partnerships have proven critical in providing end-user input to inform and improve program design. This growing network of partnerships, developed through the cultivation of personal relationships and trust over time, has also proven essential for CAPP’s rapid growth and sustainability. Overall, this Community Case Study highlights the critical role of partnerships and the importance of taking a people-centered approach, as captured in CAPP’s motto, “Connecting for Care.”